2(x-1)+3(2x-1)=7

Simple and best practice solution for 2(x-1)+3(2x-1)=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-1)+3(2x-1)=7 equation:


Simplifying
2(x + -1) + 3(2x + -1) = 7

Reorder the terms:
2(-1 + x) + 3(2x + -1) = 7
(-1 * 2 + x * 2) + 3(2x + -1) = 7
(-2 + 2x) + 3(2x + -1) = 7

Reorder the terms:
-2 + 2x + 3(-1 + 2x) = 7
-2 + 2x + (-1 * 3 + 2x * 3) = 7
-2 + 2x + (-3 + 6x) = 7

Reorder the terms:
-2 + -3 + 2x + 6x = 7

Combine like terms: -2 + -3 = -5
-5 + 2x + 6x = 7

Combine like terms: 2x + 6x = 8x
-5 + 8x = 7

Solving
-5 + 8x = 7

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + 8x = 7 + 5

Combine like terms: -5 + 5 = 0
0 + 8x = 7 + 5
8x = 7 + 5

Combine like terms: 7 + 5 = 12
8x = 12

Divide each side by '8'.
x = 1.5

Simplifying
x = 1.5

See similar equations:

| a+(b+12)= | | 12-d=5 | | 2x*x=92 | | 2(21.5-2.5y)+5y=43 | | 336/540 | | -3x^2=-4+8 | | 5j-4j=16 | | 2x/-2=-6/-2 | | 8x/5y=6 | | 3j^2+18j-48=0 | | 2(21.5+5y)+5y=43 | | 5/8m/25 | | 2x-(8x+5)=7x-31 | | sin(2x)=9.44 | | N-3/10=3/5 | | 36=k*12 | | 5/8m*25 | | 7y=33+5x | | 3u-u+3=11 | | -[10z(20z+7)]=7+(9z+8) | | 7x-3=29 | | 12(w-7)=12 | | 35=8-9*-3 | | B+4b=-9 | | 2x+30=32 | | 5v+v=12 | | 4n+6-2n=9 | | 12=3u-u | | x-(2.5/100)x=51187500 | | (17+8)-6*2= | | 6x-10-6x=10 | | 5i-6x=(10y)i+10 |

Equations solver categories